Validation of a novel robot‐assisted 3DUS system for real‐time planning and guidance of breast interstitial HDR brachytherapy. Issue 12 (6th November 2015) - Poulin, Eric; Gardi, Lori; Barker, Kevin; Montreuil, Jacques; Fenster, Aaron; Beaulieu, Luc
Abstract : Purpose: In current clinical practice, there is no integrated 3D ultrasound (3DUS) guidance system clinically available for breast brachytherapy. In this study, the authors present a novel robot‐assisted 3DUS system for real‐time planning and guidance of breast interstitial high dose rate (HDR) brachytherapy treatment. Methods: For this work, a new computer controlled robotic 3DUS system was built to perform a hybrid motion scan, which is a combination of a 6 cm linear translation with a 30° rotation at both ends. The new 3DUS scanner was designed to fit on a modified Kuske assembly, keeping the current template grid configuration but modifying the frame to allow the mounting of the 3DUS system at several positions. A finer grid was also tested. A user interface was developed to perform image reconstruction, semiautomatic segmentation of the surgical bed as well as catheter reconstruction and tracking. A 3D string phantom was used to validate the geometric accuracy of the reconstruction. The volumetric accuracy of the system was validated with phantoms using magnetic resonance imaging (MRI) and computed tomography (CT) images. In order to accurately determine whether 3DUS can effectively replace CT for treatment planning, the authors have compared the 3DUS catheter reconstruction to the one obtained from CT images. In addition, in agarose‐based phantoms, an end‐to‐end procedure was performed by executing six independent complete procedures with both 14 and 16 catheters, and for both standard and finer Kuske grids. Finally, in phantoms, five end‐to‐end procedures were performed with the final CT planning for the validation of 3DUS preplanning. Results: The 3DUS acquisition time is approximately 10 s. A paired Student t ‐test showed that there was no statistical significant difference between known and measured values of string separations in each direction. Both MRI and CT volume measurements were not statistically different from 3DUS volume (Student t ‐test: p > 0.05) and they were significantly correlated to 3DUS measurement (Pearson test: MRI p < 0.05 and CT p < 0.001). The mean angular separation distance between catheter trajectories segmented from 3DUS and CT images was 0.42° ± 0.24°, while the maximum and mean trajectory separations were 0.51 ± 0.19 and 0.37 ± 0.17 mm, respectively. Overall, the new finer grid has performed significantly better in terms of dosimetric indices. The planning target volume dosimetric indices were not found statistically different between 3DUS and CT planning (Student t ‐test, p > 0.05). Both the skin and the pectoral muscle dosimetric indices were within ABS guidelines. Conclusions: A novel robot‐assisted 3DUS system was designed and validated. To their knowledge, this is the first system capable of performing real‐time guidance and planning of breast multicatheter HDR brachytherapy treatments. Future investigation will test the feasibility of using the system in the clinic and for permanent breast brachytherapy.